2019
DOI: 10.1108/intr-06-2018-0274
|View full text |Cite
|
Sign up to set email alerts
|

A factual and perceptional framework for assessing diversity effects of online recommender systems

Abstract: Purpose The purpose of this paper is to explore the effects of online recommender systems (RS) on three types of diversity: algorithmic recommendation diversity, perceived recommendation diversity and sales diversity. The analysis distinguishes different recommendation algorithms and shows whether user perceptions match the actual effects of RS on sales. Design/methodology/approach An online experiment was conducted using a realistic shop design, various recommendation algorithms and a representative consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Instead, they observed that as users follow recommendations, their purchasing behavior becomes more similar to that of other users, as indicated by purchase similarity. Similarly, Matt et al (2014) found that perceived suggestion serendipity has a significant positive impact on both perceived preference fit and user satisfaction. Their findings suggest that simply increasing the number of innovative recommendations is not enough.…”
Section: Discussion and Findingsmentioning
confidence: 88%
“…Instead, they observed that as users follow recommendations, their purchasing behavior becomes more similar to that of other users, as indicated by purchase similarity. Similarly, Matt et al (2014) found that perceived suggestion serendipity has a significant positive impact on both perceived preference fit and user satisfaction. Their findings suggest that simply increasing the number of innovative recommendations is not enough.…”
Section: Discussion and Findingsmentioning
confidence: 88%
“…In online experiments, a web platform offering products to users, while alternative RSs make recommendations to users, is implemented. Then, the measurable effect of the used RSs on the actual users' choices is compared (Matt et al, 2013;Zhu et al, 2018;Senecal et al, 2005). Matt et al (2013) designed a website offering music tracks to users.…”
Section: Related Workmentioning
confidence: 99%
“…Then, the measurable effect of the used RSs on the actual users' choices is compared (Matt et al, 2013;Zhu et al, 2018;Senecal et al, 2005). Matt et al (2013) designed a website offering music tracks to users. They randomly assigned users to five distinct groups.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To assist users and platforms in tagging UGCs, tag recommender systems have been constructed. Recommender systems strive to simplify search processes and reduce information overflow by identifying the information that best suits user-specific preferences (Matt et al , 2019). Tag recommender systems aim at recommending informative tags for UGCs and making the tag selection process easier (Lu et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%